Cytotoxicity of dilutions of bioceramic materials in stem cells of human exfoliated deciduous teeth - Silveira, Ana Beatriz Vieira da; Oliveira, Bárbara Luísa Silva; Bergamo, Mariel Tavares de Oliveira Prado; Lourenço Neto, Natalino; Machado, Maria Aparecida Moreira; Oliveira, Thais Marchini (Journal of Applied Oral Science, 2024)
Several materials have been developed to preserve pulp vitality. They should have ideal cytocompatibility characteristics to promote the activity of stem cells of human exfoliated deciduous teeth (SHED) and thus heal pulp tissue. Objective: To evaluate the cytotoxicity of different dilutions of bioceramic material extracts in SHED. Methodology: SHED were immersed in αMEM + the material extract according to the following experimental groups: Group 1 (G1) –BBio membrane, Group 2 (G2) - Bio-C Repair, Group 3 (G3) - MTA Repair HP, Group 4 (G4) – TheraCal LC, and Group 5 (G5) - Biodentine. Positive and negative control groups were maintained respectively in αMEM + 10% FBS and Milli-Q Water. The methods to analyze cell viability and proliferation involved MTT and Alamar Blue assays at 24, 48, and 72H after the contact of the SHED with bioceramic extracts at 1:1 and 1:2 dilutions. Data were analyzed by the three-way ANOVA, followed by Tukey’s test (p<0.05). Results: At 1:1 dilution, SHED in contact with the MTA HP Repair extract showed statistically higher cell viability than the other experimental groups and the negative control (p<0.05), except for TheraCal LC (p> 0.05). At 1:2 dilution, BBio Membrane and Bio-C showed statistically higher values in intra- and intergroup comparisons (p<0.05). BBio Membrane, Bio-C Repair, and Biodentine extracts at 1:1 dilution showed greater cytotoxicity than 1:2 dilution in all periods (p<0.05). Conclusion: MTA HP Repair showed the lowest cytotoxicity even at a 1:1 dilution. At a 1:2 dilution, the SHED in contact with the BBio membrane extract showed high cell viability. Thus, the BBio membrane would be a new non-cytotoxic biomaterial for SHED. Results offer possibilities of biomaterials that can be indicated for use in clinical regenerative procedures of the dentin-pulp complex.